Local climate impacts from ongoing restoration of a peatland. Issue 3 (25th February 2022) - Worrall, Fred; Howden, Nicholas J. K.; Burt, Tim P.; Rico‐Ramirez, Miguel A.; Kohler, Tim
Abstract: We hypothesize that peatlands represent a cool humid island in their landscape context and that this cool humid island effect could be brought about by successful peatland restoration. This study used 20 years of Earth observation data for land surface temperature (day‐ and night‐ time LST), albedo (near infra‐red white sky albedo) and vegetation indices measured for 42 one km 2 grid squares across two peatlands and their surrounding arable fields. The peatlands have undergone restoration (re‐vegetation and raising of water tables) since 2004. The results show that over the restored peatlands: Day time temperatures over the peatlands cooled relative to the surrounding arable‐land by up to 1.1 K (°C), but there was no significant change in night time temperatures. Over the peatlands the average amplitude of the diurnal temperature cycle decreased by up to 2.4 K (°C) over the period of the restoration. Comparison to vegetation indices and albedo shows the cooling effect of increasing albedo was smaller than warming effect of changes aerodynamic resistance brought about by development of shrubby vegetation. The presence of an overall cooling effect, despite a warming effect due to vegetation development, means that a rising water table led to a lowering of the Bowen ratio. Peatlands revegetated to, or dominated by, moss carpets rather than shrubby vegetation will maximise the potential cooling effect, whereas shrub development across peatlands without a rise in water table would lead to warming. Abstract : This study proposed that peatlands would be cold, humid islands in a landscape. This study showed that despite shrubification of the peatland that led to a warming effect the dominant effect was changing water table leading to cooling due to changing the Bowen ratio. The restoration of the peatland led to decreases in daytime temperature and reduced amplitude of the diurnal temperature cycle.